The Role Of Teachers In Implementing Multicultural Education At Taruna Nusantara High School To Enhance Social Resilience - Robbyanandri Pratama; Siswo Hadi Sumantri; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Multicultural education has become a significant focus in enhancing social resilience at Taruna Nusantara High School. This aims to understand the role of teachers in implementing multicultural education in this school and their contribution to strengthening students' social resilience. Teachers at Taruna Nusantara High School also act as mediators in handling conflicts or tensions that may arise due to cultural differences. They play a crucial role in guiding students to understand others' perspectives, building tolerance, and enhancing effective communication skills. Teachers also provide role models in respecting differences and encourage students to become inclusive leaders in a diverse society. In the context of multicultural education, teachers at Taruna Nusantara High School also prepare students to face complex social challenges and changes. They develop a deep understanding of the values of diversity and encourage students to commit to these values. Teachers play an important role in strengthening students' social resilience, fostering multicultural understanding, and creating harmony and cooperation among students from diverse cultural backgrounds. Taruna Nusantara High School has students from various ethnicities and cultures, which bring certain advantages and disadvantages. Language differences, habits, and understandings can affect communication and collaboration among students. Moreover, a profound understanding of each ethnic group's culture and traditions is crucial to prevent stereotypes and prejudice among students. To address these challenges, Taruna Nusantara High School implements various strategies. Teachers have a central role in creating an inclusive and respectful environment. They integrate multicultural elements into the curriculum and teaching, promote open dialogue, and encourage students to understand and appreciate differences. With this rich and multicultural learning environment, Taruna Nusantara High School is able to shape students with a deeper understanding of the ethnic and cultural diversity in Indonesia. This helps strengthen students' social resilience, increase tolerance, and prepare them for living and interacting in an increasingly global and multicultural society. In this environment, students can learn to respect, appreciate, and understand differences. Thus, Taruna Nusantara High School enhances students' social resilience and prepares them to face the challenges of an increasingly multicultural world.